PENGARUH ATTACHMENT BASED FAMIY THERAPY (ABFT) TERHADAP PEMENUHAN KEBUTUHAN PSIKOLOGIS ANAK YANG MENGALAMI KETERLANTARAN DI DESA CIKOLE KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Mahatir Muhammad; Susilawati; Tuti Kartika (GoAcademica Research dan Publishing, 2021)
This study aims to examine the influence of Attachment Based FamilyTherapy (ABFT) therapy toward the Efforts to Increasing Fulfillment of children Psychological Needs Who unattended.Parent's activities to build attachments by praising, accompanying, and caressing are focus of intervention in this research. The research approach is quantitative research using Single Subjeck Design (SSD). The research model used is A-B-A which occurs from three phases of the other. Phase A1 (baseline), Phase b (Intervention), and phase A2 (result). The instrument used is the behavior observation quotation sheet. Data collection techniques such as observations, interviews, questionnaires, documentation studies and recording of permanent products. The data obtained were analyzed by way of graph making, descriptive statistics, and visual inpection analysis. Visual inspection analysis consists of analysis under conditions and inter conditions. The result of the research shows that Attachment Based Family Theapy (ABFT) application is effective to improve the attachment to the parents so that it is effective in improving fulfilling the psychological needs of the children feel they are getting the counseling, feel protected and feel accompanied. Keywords: Attachment Based Family Therapy (ABFT), praise, accompany the children. The recommendation of this research is directed to social work to deal with the problem of children less getting Atttacment from their parents. For advanced research, it is suggested to symbolize the more flexible and flexible attachment in increasing the needs of the children.